Peran Modal Sosial dalam Pengembangan Komponen Pariwisata di Desa Wisata Pentingsari - Riswandha Risang Aji; Visilya Faniza (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2022)
Indonesia is a country with abundant tourism potential where every region in Indonesia has a tourism object. Tourism itself is a sector that can utilise community capital to develop the tourism itself. One of the community capitals that can be used as a tourism attraction is social capital. Social capital is owned by regions that develop tourism, one of which is the Pentingsari Tourism Village. This research aims to describe the role of social capital in tourism development in the Pentingsari Tourism Village. The method used in this research is a case study with a qualitative approach. Data collection methods used are observation and interviews. The analysis carried out is descriptive analysis. The results of this research describe that social capital has a role in tourism development in Pentingsari Tourism Village through a social system where in principle the community develops tourism together and enjoys the benefits together as well. The system that becomes social capital is a rotating system for providing homestay and food for tourists. The conclusion of this study is that the Pentingsari Tourism Village is able to take advantage of the social capital owned by the community in the form of a rotating system to develop its tourism.